Students’ Perception Towards Instagram as English Mobile Learning: English learning, Instagram, students’ perception - Sarwoko, Gabriela Patricia; Sabudu, Delli; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This study explores students' perceptions of Instagram as a medium for English language learning, focusing on its role in enhancing engagement, creativity, and language skills. Conducted with English Education students from Universitas Negeri Manado, the research utilizes a quantitative approach and a closed-ended questionnaire, collecting data from 45 participants who actively use Instagram. The findings indicate that students perceive Instagram positively, noting its visually engaging and interactive platform as conducive to learning. Key benefits highlighted include increased engagement, enjoyment, and motivation, with Instagram’s multimedia and social features creating a dynamic environment where students feel more connected to peers and content. Additionally, Instagram is seen as a valuable tool for vocabulary acquisition and exposure to authentic English language use, particularly through real-world examples provided by native speakers and educational accounts. However, some limitations were identified, such as distractions inherent to the platform and a perceived lack of support for developing learning independence. Overall, the study suggests that Instagram holds significant potential as a supplementary educational tool, which, when thoughtfully integrated, can complement traditional methods and foster a more engaging and socially connected learning experience.